Self-Regulated Learning in Science Classes with a Discovery Learning Environment and Collaborative Discovery Learning Environment - Marina Balazinec; Ines Radanovic; Mila Bulic (MDPI AG, 2024)
The study aims to compare how discovery learning and collaborative discovery learning affect knowledge acquisition, the development of understanding through phases of self-regulated learning (SRL), and the use of SRL strategies at the individual level. The sample consists of 981 eleven-year-old students. The results show that both methods have a positive effect on knowledge acquisition. Collaborative discovery learning has more positive effects on the development of students' understanding by developing collaborative skills. Motivational strategies (especially in girls) are more developed in collaborative discovery learning than in discovery learning. Students who show more pronounced negative characteristics of self-regulation also achieve poorer results in the knowledge test, and this is more pronounced in students who have participated in discovery learning. The tendency of an affirmative attitude towards the characteristics of SRL in the entire population of students indicates a proportional growth in accordance with success in learning, but in more successful students, it indicates a uniform retention of an affirmative attitude. The tendency toward an affirmative attitude regarding the characteristics of collaborative learning is inversely proportional to students' success, with a more pronounced attitude decrease in more successful students.